Enucleation after Marsupialization: A case report of Globulomaxillary Cyst (Update Dental College Journal, 2020)
Globulomaxillary cyst found in between the roots of lateral incisor and canine of maxilla and is a non-odontogenic developmental origin. It is usually diagnosed by routine radiographic examination and it is inverted peer shaped radiolucent lesion. Adjacent teeth remain vital. Complete enucleation or marsupialization is a treatment option for this. This case report is to observe the expected results after marsupialization followed by enucleation. An eighteen years old boy noticed a painless swelling for 1 year at the left side of upper lip and we performed surgery enucleation after doing marsupialization. Here, marsupialization done to promote bone regeneration and to avoid injury to vital structures and possible fracture. Patient was followed for 3 months after enucleation and the radiolucent area was gradually reduced.This article reports the management of a globulomaxillary cyst in at two-stage procedure and it was more conservative. It might be a good treatment option for management of globulomaxillary cyst.Update Dent. Coll. j: 2020; 10 (1): 25-27